(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The recent implementation of electronic payment activity by Islamic banks, especially the issuance of electronic payment cards to bank customers of various types, is considered a new activity for Iraqi Islamic banks. Therefore, the activity is surrounded by many risks in how it is implemented, in addition to compliance with the provisions of Sharia and its principles when issuing and operating these cards and collecting the commissions assigned to their issuance. From this standpoint, the research problem emerged in the importance of the availability of an audit program that takes into account the specificity of Islamic banks and the Sharia standards that regulate their work, as well as the specificity of electronic payment activity. The research aims to provide an audit program for electronic payment activity in Islamic banks that contributes to the effectiveness of the audit process carried out by either the Federal Financial Supervision Bureau or external auditors. The tools were represented by laws, regulations and instructions related to electronic payment. As for the research sample, it was represented by the Islamic Spectrum Bank for Investment and Finance as one of the Iraqi Islamic banks licensed by the Central Bank. The research concluded that there is weakness in the procedures of the Risk Management Department in identifying and evaluating electronic payment risks and the lack of a specialized audit program for electronic payment activity and payment cards at the Federal Financial Supervision Bureau And external auditors.